Meningkatkan Aktivitas, Keterampilan Berpikir Kritis dan Hasil Belajar Peserta Didik Muatan IPA Menggunakan Model Potensi Di SDN Murung Raya 4 Banjarmasin - Muhammad Akmal Yanuari; Fathul Jannah (CV. ITTC INDONESIA, 2023)
The problem that emerged in this study was the low activity and critical thinking skills of students in Natural Sciences content which resulted in not maximizing learning outcomes. This research is a Classroom Action Research (CAR) which is carried out in 3 meetings. The method used was qualitative, the research subjects were class IVB students at SDN Murung Raya 4 Banjarmasin, totaling 16 people, consisting of 8 male students and 8 female students in semester II of the 2022/2023 academic year. The results showed that the activity of educators increased in each meeting until the indicator of success reached a score of 31 with the criteria